Teriparatide improves microarchitectural characteristics of peri-implant bone in orchiectomized rats - Gomes-Ferreira, P. H. S. [UNESP] (2020)
This study evaluated the peri-implant bone repair in orchiectomized rats receiving intermittently PTH 1-34. The treatment returned the bone quality and quantity of the animals to normal in the computerized microtomography, laser confocal microscopy, and histological analysis. The PTH 1-34 promoted marked bone formation with increased volume, improved quality, and greater bone turnover. Introduction Osteoporosis can be a problem in implant osseointegration. So this study aimed to evaluate the quantity and quality of peri-implant bone repair in orchiectomized Wistar rats receiving intermittently administered PTH 1-34. Methods Animals (n = 24) were divided into 3 groups: healthy control (SHAM), orchiectomized (ORQ), and orchiectomized and treated with 0.5 mu g/kg/day PTH 1-34 (TERI), and each received an implant in the right and left tibial metaphysis, which was allowed to repair for 60 days. The resultant bone formation was evaluated through computerized microtomography (micro-CT) to compare the percent bone volume (BV/TV), trabecular thickness (Tb.Th), trabecular number and separation (Tb.N, Tb.Sp), and bone implant contact (BIC) through the intersection surface (i.S) between groups. Laser confocal microscopy was used to evaluate fluorochrome areas for mineral apposition rate (MAR) and neoformed bone area (NBA). In addition, histological evaluation of calcified tissues with Stevenel blue and alizarin red staining was performed. Results Treatment with PTH 1-34 returned the bone quality and quantity of the osteoporotic animal to normal, as the TERI group presented statistically significant higher values for BV/TV, Tb.Th, and BIC parameters compared with ORQ (p < 0.05), but when compared with SHAM (p > 0.05), no statistical difference was noted. In addition, in the bone turnover analysis (MAR, NBA) for TERI, the highest results are presented, followed by SHAM, and then ORQ (TERI x ORQ: p < 0.05). Conclusions Intermittent treatment with PTH 1-34 on orchiectomized animals promoted marked bone formation with increased volume, improved quality, and greater bone turnover in the peri-implant space, returning the bone quality and quantity to the present standard in healthy animals.